2012
DOI: 10.4038/cjsbs.v40i2.3934
|View full text |Cite
|
Sign up to set email alerts
|

Invasion by <i>Austroeupatorium inulifolium</i> (Asteraceae) arrests succession following tea cultivation in the highlands of Sri Lanka

Abstract: An understanding of floral succession is vital in planning the restoration of native vegetation in abandoned agricultural landscapes. Although such restoration is essential for the establishment of habitat corridors between the fragments of tropical montane cloud forest in the Sri Lankan highlands, in which > 90% of the land has been converted to tea plantations, no studies of succession have hitherto been possible because of the near-total absence of secondary forest in this region. In a pioneering restoratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The Galapagos have a dryer climate and much lower forests than in our study area, and these environmental differences may influence the success of its invasion. The only true liana among the invasive species was Passiflora suberosa, although the herb M. cordata grows as vine ( Sri Lanka (Pethiyagoda and Nanayakkara 2011). The dominance of these shade-intolerant herbs, however, is achieved on the time scale of several decades.…”
Section: Species Characteristicsmentioning
confidence: 99%
“…The Galapagos have a dryer climate and much lower forests than in our study area, and these environmental differences may influence the success of its invasion. The only true liana among the invasive species was Passiflora suberosa, although the herb M. cordata grows as vine ( Sri Lanka (Pethiyagoda and Nanayakkara 2011). The dominance of these shade-intolerant herbs, however, is achieved on the time scale of several decades.…”
Section: Species Characteristicsmentioning
confidence: 99%
“…It can be caused by transect location along human trail which faciletate A. inulifolium spread into interior forest. A. inulifolium commonly found at roadsides, agricultural fields and abandoned lands [16]. Furthermore, A. inulifolium is reported as invasive species in Sri Lanka and in Indonesia at Alas Purwo National Park and Mt.…”
Section: Proximity From Botanical Garden and Forest Structure On Non-mentioning
confidence: 99%
“…Furthermore, A. inulifolium is reported as invasive species in Sri Lanka and in Indonesia at Alas Purwo National Park and Mt. Halimun Salak National Park [16,17,18] and in Mt. Gede Pangrango National Park this Asteraceae member was naturalized [19].…”
Section: Proximity From Botanical Garden and Forest Structure On Non-mentioning
confidence: 99%
“…Such restoration could, in the dry zone, be achieved in as little as three decades (Cramer, 1993), whereas in the wet and montane zones succession occurs over much longer time frames (Pethiyagoda and Nanayakkara, 2011). In any event, it seems likely that increasing urbanization will precipitate an increase in the extent of secondary vegetation, though the relationship between urban population growth and the generation of secondary forest is too complex to be predicted reliably (Brook et al, 2006).…”
Section: Despite Continued Forest Conversion and Degradation Forest mentioning
confidence: 99%
“…Indeed, even in Sri Lanka, grasses, ferns and alien plants feature prominently in successional vegetation (see Gunaratne et al, 2010). At a former tea plantation in Agrapatana (elevation 1540-1780 m), for example, Pethiyagoda and Nanayakkara (2011) found that 10 years after the removal of tea, 96% of woody stems represented alien species. Nevertheless, this 25 ha site harbours a substantial proportion of vertebrates found in oldgrowth montane forest, including 12 of the 15 amphibian species that occur in the nearby AgraBopath Forest Reserve (pers.…”
Section: Conservationmentioning
confidence: 99%